THE NATURE OF EDUCATORS AND STUDENTS IN ISLAMIC EDUCATION - Ihwan, Muh.; Muis, Andi Abd.; Mansur, Budi; Nasriadi, Nasriadi; Darwin, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the Islamic concept of the nature of educators and students. Why is this research interesting to discuss? The Islamic concept of the nature of educators and students is very important in the world of Islamic education so that Islam is very strict in paying attention to the Islamic concept of the nature of educators and students. Therefore, the author explains how important the concept of education is in the future as a superior investment to continue the preservation of civilization as an educated generation. To obtain effective education as an effort to produce great and competent educators and students, Islam explains the nature of educators and students. In terms of methodology, this article is a type of library research. Furthermore, this study is basically library research. The data analysis used in this research is content analysis, namely analyzing the contents of the book. Another method used is the critical comparison method, namely comparing the thoughts of experts. From this research, the results obtained are that among the verses about Islamic concepts regarding educators and students are found in Q.S Al-Alaq verses 1-4. Education is a process of humanization as well as a conscious effort to develop human physical and non-physical potential. On the other hand, Islamic education is basically the instilling of Islamic teaching values in students, namely the Al-Qur'an and Hadith.